2005
DOI: 10.1007/s00127-005-0966-2
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with ideation and acts of deliberate self-harm among 18-year-old boys

Abstract: The connection between self-reported depressive symptoms at age 8 and ideation and acts of deliberate self-harm at age 18 is a good reason to already pay special attention to children's own intimations of distress in elementary school. It is likely that an effective way to prevent suicidality among adolescents is to search for and treat psychiatric problems among young people. Self-reported screening questionnaires used, e.g. in school healthcare, may provide an opportunity to recognize these problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
77
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 32 publications
6
77
0
2
Order By: Relevance
“…found higher levels of depression in those suicide attempters who had a history of self-mutilation compared with a control suicidal group. In the study of Haavisto et al [18] selfreported depressive symptoms at the age of eight predicted acts of DSH 10 years later. One of the few exceptions is the study of suicide attempters by Langbehn and Pfohl [24] where mutilators were less likely to have diagnoses of major depression than non-mutilating suicidal peers.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…found higher levels of depression in those suicide attempters who had a history of self-mutilation compared with a control suicidal group. In the study of Haavisto et al [18] selfreported depressive symptoms at the age of eight predicted acts of DSH 10 years later. One of the few exceptions is the study of suicide attempters by Langbehn and Pfohl [24] where mutilators were less likely to have diagnoses of major depression than non-mutilating suicidal peers.…”
Section: Discussionmentioning
confidence: 98%
“…Nonfatal deliberate SI or self-harm is not only most common in young people, especially young females [20,42], but is also the most frequent diagnosis among adolescent females in outpatient psychiatric facilities [18,20,21,25]. Ross and Heath [40] stress that 13.9% of students, especially girls, in community samples report self-mutilation.…”
Section: Introductionmentioning
confidence: 99%
“…So far, there are only a few prospective studies of emotional risk factors for selfharm. In one study [18], self-reported depressive symptoms at the age of 8 were found to predict acts of self-harm 10 years later in a community-based sample of 2,348 boys. In another study [19], predictors at the age of 12 for acts of self-harm at the age of 15 were studied; the results showed that self-reported internalizing problems and somatic complaints, as well as parent-reported externalizing problems and aggressiveness, independently predicted selfreported acts of self-harm 3 years later.…”
Section: Introductionmentioning
confidence: 98%
“…Prospective studies revealed that mental health problems in childhood (whether self-reported or by parents or teachers) are predictive for mood disorder later on [38,39]. Thus, detecting and offering early help to children, adolescents and young adults that suffer under mental health symptoms is recommended [40].…”
Section: Indicated Preventionmentioning
confidence: 99%